Language Games to Improve Students’ Classroom Interactions (2024)
ABSTRACT: This action research was conducted at “Institución Educativa Francisco Luis Hernández Betancur'' with 31 students between 11 and 13 years old. It was aimed at evaluating the effectiveness of language games to improve classroom interactions among sixth graders. Data was collected through a personal journal in which I registered detailed descriptions of the observations and some reflections regarding the research objectives; a four-question survey applied after each language game implementation to the students; a semi-structured interview with the cooperating teacher to know his perspective of the strategy; students’ self-assessment rubric and video recordings that were useful to analyze the students’ interactions. Data analysis showed that language games were a successful activity for fostering an enjoyable environment for learning English. Besides, students’ classroom interaction showed an improvement in which students were evident to interact more among themselves and helped each other during the development of the activity. Finally, language games were also effective in promoting students’ participation in which students were motivated to take part in the class activities.